Control of CMG crane using model error compensator to measure 3D digital model of ISHIGAKI stones of Kumamoto Castle - Nobutomo MATSUNAGA; Naufal Bayu FAUZAN; Hiroshi OKAJIMA; Gou KOUTAKI (Nihon Kikai Gakkai ronbunshu, 2021)
Kumamoto Castle, consisting some towers and the stone walls called ISHIGAKI, was severely damaged by Kumamoto earthquake in 2016. As Kumamoto Castle has some important cultural properties of Japan, prompt and accurate restoration works for the damaged stone walls and the castle are needed. For the restoration works, it was difficult to estimate all collapsed stone locations since the shapes of the stones are similar. For this problem, the estimation method of possible stones based on iterative closest point algorithm using photographic imagery has been studied. This algorithm showed a good result, however, about 20% of collapsed stones were not decided. In recent years, the utilization of stone’s 3D data has been studied to recognize of the possible stones precisely. For an efficient renovation, it is needed to measure 3D data automatically in a short period of time. In this paper, the scanning system of the collapsed stones controlled by a compact control moment gyroscope (CMG) crane and an elevator to move 3D scanner is proposed. Parameter change of CMG crane which caused by the stone shape and size is suppressed by the model error compensator (MEC). The CMG crane rotates the stone around according to the up-and-down motion of the 3D scanner moved by an elevator. The effectiveness of the proposed system to archiving 3D data is evaluated by scanning dummy stones experiments.